2007
DOI: 10.3748/wjg.v13.i39.5180
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic steatosis as a possible risk factor for the development of hepatocellular carcinoma after eradication of hepatitis C virus with antiviral therapy in patients with chronic hepatitis C

Abstract: AIM:To elucidate risk factors contributing to the development of hepatocellular carcinoma (HCC) among patients with sustained viral response (SVR) after interferon (IFN) treatment and to examine whether HCV-RNA still remained in the liver of SVR patients who developed HCC. METHODS:Two-hundred and sixty-six patients, who achieved SVR, were enrolled in this study. We retrospectively reviewed clinical, viral and histological features of the patients, and examined whether the development of HCC depends on several … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
54
4
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 42 publications
1
54
4
1
Order By: Relevance
“…There have also been many studies on the risk factors for the development of HCC after SVR has been achieved [16,17,18,19]. Some studies found that elevated AFP level at baseline, older age, male gender, and advanced stage of liver fibrosis were independent risk factors for HCC in patients with HCV infections [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…There have also been many studies on the risk factors for the development of HCC after SVR has been achieved [16,17,18,19]. Some studies found that elevated AFP level at baseline, older age, male gender, and advanced stage of liver fibrosis were independent risk factors for HCC in patients with HCV infections [20,21].…”
Section: Discussionmentioning
confidence: 99%
“…However, it is not clear whether the same factors are also responsible at cirrhotic staging [30,31]. It was reported that alcohol [32], occult infection with hepatitis B virus (HBV) [33], and hepatic steatosis [34] could maintain hepatocyte turnover after the eradication of HCV and increase the risk for HCC.…”
Section: Introductionmentioning
confidence: 98%
“…Previous studies have demonstrated the association between metabolic syndrome and hepatic fibrosis in patients with hepatitis C (6)(7)(8)(9)(10)(11). Steatosis is a frequent histological finding in chronic hepatitis C virus infection, one that affects disease progression and occurrence of hepatocellular carcinoma (7,(12)(13)(14)(15). Hepatic steatosis is associated with metabolic syndrome and non-alcoholic steatohepatitis (NASH).…”
Section: Introductionmentioning
confidence: 99%